تأثير الدور الحوكمي لمجلس الإدارة في تحسين القيمة الملائمة لدوافع الاعتراف باضمحلال قيمة الأصول المالية وذلك من منظور المستثمرين: دراسة تطبيقية على الشركات المساهمة المصرية - علي، عرفات حمدي عبدالنعيم Ali, Arafat Hamdi Abdulnaim (جامعة طنطا - كلية التجارة - قسم المحاسبة, 2019)
يهدف البحث بصفة أساسية إلى بيان تأثير سمات وخصائص مجلس الإدارة كإحدى ممارسات الحوكمة الداخلية على تحسين القيمة الملائمة لدوافع الاعتراف باضمحلال قيمة الأصول المالية، ولتحقيق هذا الهدف قام الباحث بتصميم نموذجين رياضيين، حيث يعكس النموذج الأول العلاقة بين سمات وخصائص مجلس الإدارة كمتغير مستقل ومستوى الاعتراف باضمحلال قيمة الأصول المالية كمتغير تابع وبالاعتماد على حجم الشركة كمتغير. رقابي، بينما يعكس النموذج الثاني العلاقة بين مستوى الاعتراف باضمحلال قيمة الأصول المالية كمتغير مستقل وقيمة الشركة وفقا لمقياس Tobin's Q كمتغير تابع وبالاعتماد على سمات وخصائص مجلس الإدارة كمتغير رقابي أو معدل، وذلك لعينة من الشركات المساهمة المقيدة في البورصة المصرية خلال الفترة من عام 2013م وحتى عام 2017م. وتشير نتائج البحث إلى وجود تأثير معنوي لغالبية سمات وخصائص مجلس الإدارة على مستوى الاعتراف باضمحلال قيمة الأصول المالية، هذا بالإضافة إلى وجود تأثير معنوي لمستوى الاعتراف باضمحلال قيمة الأصول المالية على قيمة الشركة، وذلك من خلال تضمين سمات وخصائص مجلس الإدارة كمتغير رقابي أو معدل للعلاقة بين المتغير التابع والمتغير المستقل، مما يعكس الدور الهام والفعال لمجلس الإدارة كأحد آليات الحوكمة الداخلية في تحسين قيمة المعلومات المفصح عنها بشأن اضمحلال قيمة الأصول المالية وذلك من وجهة نظر المستثمرين. كما تسهم نتائج البحث في توفير دليل عملي من البيئة المصرية بشأن أهمية وتأثير سمات وخصائص مجلس الإدارة في تحسين نفعية المعلومات المتعلقة باضمحلال قيمة الأصول المالية خاصة عند تقييم ممارسات إدارة الأرباح التي تقوم بها الشركات. الأمر الذي ينعكس على تحسين مستوى إدراك الشركات لأهمية توافر خصائص الحوكمة الفعالة لمجلس الإدارة، وبما يؤدي إلى تعظيم قيمة الشركة في الأجل الطويل.
This study aims to investigate the impact of directors Board characteristics as internal corporate governance (CG) practices in improving the value relevance of the recognition of financial assets value impairment. To do so, we designed two mathematical models, the first model reflects the relationship between the directors Board characteristics as an independent variable and the level of recognition of Financial assets value impairment as a dependent variable and depending on the firm size as a control variable, while the second model reflects the relationship between the level of recognition of Financial assets value impairment as an independent variable and the firm value according to the measure of Tobin's Q as a dependent variable and based on the directors Board characteristics as a control or moderate variable, using a sample including the companies listed in the Egyptian Stock Exchange during the period from 2013 to 2017. The study results indicate that there is a significant effect on the majority of the Directors Board characteristics on the level of recognition of financial assets value impairment. There is also a significant effect to the level of recognition of the financial assets value impairment on the firm value by including the Directors Board characteristics as a control or moderate variable, Which reflects the important and effective role of the Directors Board as an internal governance mechanisms in improving the disclosed information value about financial assets value impairment from an investor perspective. The study results also contribute to providing practical evidence from the Egyptian environment on the importance and impact of the Directors Board characteristics of in improving the information usefulness about the financial assets value impairment, especially in evaluating profit management practices by companies. Which is reflected in the improvement of the companies' awareness level about the importance of effective governance Directors Board characteristics, which leads to maximizing the firm value in the long term.
Keywords: مصر -- شركات المساهمة -- الأصول المالية -- حوكمات الشركات -- مجالس الإدارة